Modeling discontinuous growth in reared Panulirus ornatus: a generalized additive model and cox proportional hazard model approach - Foo, Chuan Hui (Tanjung Malim, 2023)
Modeling discontinuous growth in reared Panulirus ornatus: a generalized additive model and cox proportional hazard model approach by Foo, Chuan Hui